Control of traction supply power quality using locomotive PWM converter controls - Kuppa, V.; Wolfs, Peter; Senini, S. (University of Canterbury NZ, 2003)
Railway traction systems are highly susceptible to severe harmonic distortion, poor voltage regulation and line resonances. Electric locomotives, which are concentrated high power loads, move continuously along the supply line, rendering the topography of the supply system, a time-variable. Under those conditions, the resonant impedances vary as the traction vehicle moves along the track. Parallel resonances with feeder line inductance and capacitance between feeder line and earth, cause harmonic magnification. This paper will examine the use of small retrofit converters to improve the performance of multiphase PWM rectifiers as found in locomotive applications.